2000
DOI: 10.1159/000016359
|View full text |Cite
|
Sign up to set email alerts
|

Signalling Mechanisms Involved in Volume Regulation of Intestinal Epithelial Cells

Abstract: Most mammalian cells have developed compensatory mechanisms to respond to the variable osmotic stress caused by changes in the concentrations of intracellular osmo-active substances (e.g. glucose, amino acids, lactate) or by variations in the osmolarity of the surrounding medium. In response to osmotic cell swelling, the Regulatory Volume Decrease (RVD) is triggered and directs a reduction in the tonicity of the cell by the concerted opening of cation and anion selective ion channels. To date, the K+ Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 47 publications
2
30
0
Order By: Relevance
“…MAP kinase inhibitors did not alter RVD upon hypoosmolarity in intestinal epithelial cells [54] and it is therefore suggested that osmosignalling towards RVD is cell-specific. The exact nature of the residual nonp38 MAPK -dependent RVD in liver still mains to be elucidated.…”
Section: Discussionmentioning
confidence: 91%
“…MAP kinase inhibitors did not alter RVD upon hypoosmolarity in intestinal epithelial cells [54] and it is therefore suggested that osmosignalling towards RVD is cell-specific. The exact nature of the residual nonp38 MAPK -dependent RVD in liver still mains to be elucidated.…”
Section: Discussionmentioning
confidence: 91%
“…Stretch-activated ion channels (SAC) may be activated as a direct response to membrane stretch. [89], whereas in human cervical cancer cells hypotonicity-induced elevation of Ca i by entry from the extracellular medium is a prerequisite for normal RVD [90]. In the latter cell type the hypotonicity-induced Ca 2+ signalling and the swelling-dependent Cl -and taurine release were found to require myosin light chain kinase (MLCK) activity, but did not correlate with MLC phosphorylation, which implies that MLCK controls Ca 2+ signalling by an MLC phosphorylation-independent mechanism [90].…”
Section: Intracellular Calcium (Ca I ) Levelsmentioning
confidence: 93%
“…This indicates that in these cells the swelling-induced ATP release is independent of RVDC activation. Furthermore auto/paracrine ATP signaling does not activate RVDC in human intestine 407 cells, however, the ATP signaling via P2Y receptors is responsible for swellinginduced Erk1/2 activation [89,157] and can potentiate the rise of Ca i in response to hypotonic swelling by stimulating cellular Ca 2+ entry via volume-sensitive cation channels and by release from intracellular stores [86]. In rat hepatocytes and HTC hepatoma cells, the volumesensitive ATP release is inhibited by Gd 3+ .…”
Section: Autocrine Regulation Of Rvd By Hormones and Transmittersmentioning
confidence: 95%
See 1 more Smart Citation
“…Most cell types respond immediately to osmotic changes by activating plasma membrane transport pathways leading to net accumulation (upon hyperosmotic stress) or loss (upon hyposmotic stress) of osmotically active intracellular solutes (11,43). The mechanism(s) whereby altered intracellular osmolarity interferes with physiological mammalian cell functions such as proliferation and differentiation is(are) poorly understood.…”
Section: Effect Of Changes In Extracellular Osmosis On Cell Growth-mentioning
confidence: 99%